Technology impact some thoughts on deskilling and design responsibility. - Frazzini, Ron (IEEE Control systems magazine)
The marketing pitch promotes the positive results when new technology is developed and in the hands of the user. Rarely does it discuss potential human interaction problems that might result from its application-matters that are outside the scope of the technical design specification. Since new technology typically evolves due to entrepreneurial efforts or reaction to customer demand, we seldom look beyond specification boundaries to carefully evaluate subtle product use consequences. Indeed, many believe that market evaluation, with its cost-benefit analysis, is all that is necessary, but the effects of new technology on culture and the individual are almost never part of these analyses because they are difficult to define in dollar values. Certainly, environmental impact and safety are high on the list of public concerns. Further down the list are the effects of product characteristics on human response and behavior.